Physiological and Biochemical Changes Analysis to Labors Blood Samples in Plastics Recycling Factory in Mosul-Iraq - Muwafaq Ayesh Rabeea (Journal of Global Pharma Technology, 2018)
In this study, the healthy impacts of environmental and emitted pollutants from the recycling plastics factories in the Right Bank district of Mosul City were investigated. Urine and blood samples were collected from workers who exposed to these pollutants. Some of physiological and biochemical tests have been achieved which including Blood Pressure, Hb (Hemoglobin), PCV, ESR, blood urea, serum total protein, serum total cholesterol, serum triglycerides, ALT (GPT) and AST (GOT). Also, General Urine Examination has been performed. All results were compared with 20 unaffected persons as a control group. The results of the current study showed significant differences in some testes compared with the control group. Hemoglobin increased to ‏17.00 g/dl in the workers which had >20 years-work compared with the control (14.00 g/dl). Furthermore, PCV have a significant increase ranging from 55.53% to 90.53% in workers who have <10, 11-20 and >20 years-work. Blood Urea recorded highest value ‏50 g/dl for workers >20 years-work, while declined to the lowest value 37 g/dl in case <10 years-work. Also, liver enzymes (Aspartate Transaminase and Alanine Transaminase) were recorded slight increase reached to 13.3 and 6.6 IU/dl respectively. In addition, General Urine Examination exhibited various kinds of cells besides highest percentages of Calcium Oxalate, pus cells, amorphous and RBC (Red Blood Cells) reached to 40.85%, 13.85%, 8.71% and 3.85% respectively.Keyword: Emitted pollutants; Plastics wastes; Biological & chemical effects; Damage enzymes.